Assessment of the prevalence of nootropic drugs by elderly patients in geriatric practice - Emilia Główczewska-Siedlecka; Jadwiga Główczewka; Katarzyna Mądra-Gackowska; Marcin Gackowski; Krystyna Nowacka; Zygmunt Siedlecki; Mateusz Szostak; Kornelia Kędziora-Kornatowska (Kazimierz Wielki University, 2017)
So-called nootropics include a diverse group of drugs whose idea is to improve brain function. They are quite commonly accepted among the elderly. Although currently available data from the literature do not show unequivocally the efficacy of these drugs, in practice a large number of patients are in practice. These drugs are prescribed to patients fairly commonly and the range of indications for their use is wide and non-specific. This publication presents the mechanism of action of these nootropic drugs, historical outline of their use and epidemiological data on their use in elderly patients on the basis of patients treated in the Department of Geriatrics of Medical University in Bydgoszcz.